Failing in the system or systemic failure? The inherent tension within surgical trainee underperformance and remediation - Zhu, Alison; Aitken, Sarah Joy (The American journal of surgery, 2024)
Yet, as McLeod et al. describe in this issue of The American Journal of Surgery, the experience of remediation can frequently be isolating, confusing, and overly punitive for surgical trainees.1 The need for remediation almost always results in negative emotions, particularly shame, anxiety, and guilt.2 These emotional challenges from remediation are not unique to Australia and are reported in training programs globally.3,4 It is reassuring that most trainees who undertake remediation effectively progress and, at the end of training, are indistinguishable from non-remediated peers.5,6 However, as McLeod et al. report, the negative emotional impact of remediation can be long-lasting, even continuing after successful reintegration into training programs.1 Remediation is a highly stressful time and resource intensive undertaking, and despite increasing scholarly understanding of remediation, the evidence supporting effective methods remains limited.3,7–9 As surgical training programs reconfigure towards competency-based medical education (CBME), careful consideration is required as to how remediation fits within the structural context and experience of training.10,11 Remediation positions trainees in a liminal space, or ‘island’, outside of the normal progression of unimpeded training and subject to additional assessment and scrutiny.12 In McLeod et al., trainees describe this space as lonely, isolated, and disempowering.1 For trainees from gender identities or racial and ethnic backgrounds who are underrepresented in medicine, this exclusion can be further exacerbated by implicit bias and systemic racism.13 Although temporary, the greater scrutiny, loss of self-regulated education, and high stakes nature of remediation are deeply personal.13 Programs of remediation designed to educate and support, also set trainees apart from their peers and have the unintended consequences of stigma and disempowerment.1,7 This tension between educational goals and regulatory strictures can significantly challenge the professional identity of trainees and clinicians in remediation programs.14,15 Successful remediation is hindered by emotions such as shame, anger, and regret.8 For trainees undergoing remediation, confidential discussions that acknowledge the negative emotions associated with underperformance can build psychological safety and improve readiness to change.8 It is imperative that remediation – correcting ‘failure in the system’ - is connected to the broader debates and shifting perspectives in medical education - correcting ‘systemic failure’.4,12,14 Hidden curriculum, societal and professional expectations, and institutional structures influence the nature and implementation of remediation programs.16 In traditional, time-based training programs, progression is dependent on linear acquisition of skills at defined intervals, with little flexibility afforded to trainees who are struggling to consolidate learning.12 Trainees who deviate from the ‘correct’ pathway are seen as failing, risking professional censure and exclusion.17 This strong emphasis on individual remediation neglects the situated and contextual influences on performance (or lack thereof). Within clinical service heavy professions like surgery, the risk of failure increases for struggling learners as they attempt to manage training and employment demands.2,4,18 The competency of surgical teams, workplace culture, and complex systems in healthcare play a substantial role in trainee performance. Applying this model to CBME, assessments, such as entrustable professional activities (EPAs), facilitate longitudinal opportunities for feedback and early, informal performance correction.11 This increase in feedback provided to trainees creates the necessary educational scaffolding to support trainee learning and progression and may also reduce the feeling of being ‘blindsided’ by negative performance assessment that was described by McLeod et al.‘s participants.1,3 Improving trainee experiences and outcomes from remediation requires program transparency and flexibility.